مسار بعض المتغيرات التنموية في ظل التحول إلى "اقتصاد السوق الاجتماعي" في سورية - نجوم, أسامة (Latakia University Journal - Economic and Legal Sciences Series, 2014)
لقد شهدت نتائج تجربة اقتصاد السوق الاجتماعي في سورية جدلاً حادًا بين من هو مدافع عنها ومن ينتقدها بشدة. ويهدف هذا البحث لإجراء تقييم موضوعي ومحايد للتجربة التنموية القائمة على اقتصاد السوق الاجتماعي من خلال استعراض مسار مجموعة من المتغيرات التنموية خلال الفترة 2005-2010. وقد توصل البحث إلى أن جوانب الإخفاق في تجربة اقتصاد السوق الاجتماعي أكثر من جوانب النجاح، فعلى الرغم من نجاحها في تحقيق معدلات نمو مقبولة للناتج الحقيقي؛ وتقليص حجم الدين الخارجي؛ وزيادة حجم احتياطات القطع الاجنبي، فإنها لم تنجح في تعزيز هيكلية الاقتصاد السوري وترسيخ مقومات نمو مستدام يتماشى مع الزيادات السكانية. وقد أخفقت هذه التجربة في إيجاد سوق عمل مرنة قادرة على تلبية الطلب المتزايد على فرص العمل، وفي تخفيض معدلات الفقر وفي تحسين القدرة الشرائية للأفراد. The results of social market economy exercise in Syria have been arguably debated. Some took a firm stand in defending it, while others harshly criticized it. This research aims at providing an unbiased assessment of the social market economy exercise by reviewing some developmental indictors over the period 2005-2010. The outcomes of this research indicate that the failures outweighed the successes. Although, the social market economy exercise resulted in good rates of output growth, reduced the volume of the external debt, and increased the total foreign reserves. However, it failed in enhancing the structure of the Syrian economy, and in promoting a sustainable growth that is capable of matching the population rise. Also, it failed in creating a flexible labour market that provides jobs, and it failed in reducing poverty rates and improving purchasing power of the individuals.